2007
DOI: 10.1359/jbmr.061203
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for BMD and Bone Strength in an Intercross Between Domestic and Wildtype Chickens

Abstract: With chicken used as a model species, we used QTL analysis to examine the genetic contribution to bone traits. We report the identification of four QTLs for femoral traits: one for bone strength, one for endosteal circumference, and two affecting mineral density of noncortical bone.Introduction: BMD is a highly heritable phenotype, governed by elements at numerous loci. In studies examining the genetic contribution to bone traits, many loci have been identified in humans and in other species. The goal of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 45 publications
1
57
1
Order By: Relevance
“…The superior bone strength of Ross birds over Cobb, which prevailed irrespective of whether comparisons were made at the same photoperiod, same body weight, or same ash content, probably indicates a more successful selection for bone strength in the Ross than in the Cobb birds; a quantitative trait locus for bone biomechanical strength has been identified on chromosome 20 of domestic fowl (Rubin et al, 2007). What is not clear, is why the differences in tibial breaking strength between Ross and Cobb birds were so much greater under 512-h than under !12-h photoperiods ( Figure 1); body weights for the two genotypes were not significantly different , so greater body weights were not an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…The superior bone strength of Ross birds over Cobb, which prevailed irrespective of whether comparisons were made at the same photoperiod, same body weight, or same ash content, probably indicates a more successful selection for bone strength in the Ross than in the Cobb birds; a quantitative trait locus for bone biomechanical strength has been identified on chromosome 20 of domestic fowl (Rubin et al, 2007). What is not clear, is why the differences in tibial breaking strength between Ross and Cobb birds were so much greater under 512-h than under !12-h photoperiods ( Figure 1); body weights for the two genotypes were not significantly different , so greater body weights were not an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…One red jungle fowl male was mated to three White Leghorn females, producing 1046 F 2 offspring in total, 827 of which had measured genotypes. This population has previously been used in QTL mapping for behavior traits (Schü tz et al 2002), egg production (Wright et al 2006), and morphology Kerje et al 2003;Rubin et al 2007) and a full description of the mapping population can be found in those references.…”
Section: Biological Materialmentioning
confidence: 99%
“…Linkage analysis has successfully identified numerous quantitative trait loci (QTLs) associated with skeletal traits, including bone morphology and dimensions, (2)(3)(4)(5)(6)(7)(8) BMD, (9)(10)(11)(12) bone mechanical properties, (13)(14)(15)(16)(17) and trabecular bone architecture. (18,19) Multiple QTLs affecting length are also known and frequently map to loci associated with BMD or total body size.…”
mentioning
confidence: 99%